IMPACT OF IMPLEMENTING INFORMATION TECHNOLOGY ON TEACHING IN PUBLIC SECONDARY SCHOOLS IN MBEERE SUB-COUNTY, EMBU COUNTY, KENYA - Murungi, Verasia Mukwaiti; Kibaara, Dr. Tarsilla M.; Mwaniki, Terry M. (IJRDO- Journal of Educational Research, 2017)
The significant role of information and communication technology (ICT) in education has beenimproving and the Kenyan Government has developed policies and initiatives to institute the useof ICT’s in schools and this study therefore sought to establish the impact of implementinginformation technology on teaching in public secondary schools by examining the impact of ICTin teaching. The findings of the study showed that although the government established ICTpolicies to enhance use of ICT, secondary schools in the Sub County have not adequatelyimplemented ICT in teaching, with the study showing that teachers lacked the necessary skillsfor the ICT uptake, though the they have the will and commitment to roll out the ICT policy asdirected by the Ministry. The study recommends that teachers need to be supported throughtraining on ICT skills necessary for teaching, and that computer applications to form part of theteacher training curriculum.